Medical Emergency Management in Dental Practice: Proactive Risk Stratification and Simulation-Driven Clinical Readiness - Dwi Riski Saputra; Hendrijaya Permana; Zainul Cholid (Al-Hijrah Indonesia, 2026)
The increasing prevalence of geriatric patients with complex comorbidities and polypharmacy has significantly elevated the incidence of chairside medical emergencies in dental practice. Although oral and maxillofacial surgeons possess comprehensive theoretical knowledge of the pathophysiology underlying emergencies such as vasovagal syncope and hypoglycemia, a critical